EFL LEARNERS’ ATTITUDES TOWARDS THE IMPROVEMENT OF THEIR ENGLISH SPEAKING PERFORMANCE - Mahripah, Siti (LITERA, 2013)
This study aims to describe EFL learners’ attitudes towards the improvement of their English speaking performance. The data were collected through a questionnaire distributed to 131 students of Department of English Language Education. The results of the dataanalysis show that all respondents show positive attitudes towards the improvement of their English speaking performance. Although female students have more positive attitudes than male students, the difference is not significant. The results also show that students’ attitudes towards their speaking performance change in accordance with their learning time. Their self-assessment of their speaking performance has a significant correlation with their attitudes. Their positive attitudes towards the improvement of their English speaking performance serve as a foundation to the success of the English language learning. Therefore, learners should pay attention to and maintain attitudes to improve their speaking performance.